Comparison of Complication Rates, Types, and Average Tube Patency Between Jejunostomy Tubes and Percutaneous Gastrostomy Tubes in a Regional Home Enteral Nutrition Support Program. (6th November 2014) - Ao, Peter; Sebastianski, Meghan; Selvarajah, Vijeyakumar; Gramlich, Leah
Abstract : Background: Percutaneous endoscopic gastrostomy (PEG) tubes are common enteral access devices for long‐term enteral nutrition. Jejunostomy tubes (J‐tubes) are able to provide postpyloric enteral access in patients who are not PEG tube candidates. There is a scarcity of literature comparing complication rates of J‐tubes to PEG tubes. Objective : To compare and characterize J‐tube and PEG tube complications requiring tube replacement. Methods : A retrospective chart review was performed on 560 patients discharged from the Northern Alberta Home Enteral Nutrition Support Program (NAHENSP) from January 2010 to December 2011. Patients were followed for 3 years from initial tube insertion or until discharge from the NAHENSP, whichever was earliest. Comparisons were made in terms of complications requiring tube replacement, tube patency to first replacement, and indications for tube replacement. Results : A total of 64 J‐tube patients were identified and compared with 65 PEG tube patients. Tube replacement rates for the J‐tube group included 3.2 cases per 1000 patient days compared with 0.86 cases per 1000 patient days in the PEG group ( P < .001). The mean ± SEM duration to first tube replacement for J‐tube and PEG tube patients was 160 ± 26.3 days and 331 ± 53.6 days, respectively ( P = .010). The most common causes for tube replacement in J‐tube patients were dislodgement (35.6%) and obstruction (22.2%) compared with routine replacement (54.5%) and dislodgement (27.2%) in the PEG tube group. Conclusion : J‐tubes are associated with higher complication rates requiring tube replacement compared with PEG tubes. The main causes of J‐tube replacement are dislodgement and obstruction.